ヒョウショウ シンソウ クッサク ドリル ノ カイハツ III - 高橋, 昭好; タカハシ, アキヨシ; 藤井, 理行; フジイ, ヨシユキ; 成田, 英器; ナリタ, ヒデキ; 田中, 洋一; タナカ, ヨウイチ; 本山, 秀明; モトヤマ, ヒデアキ; 新堀, 邦夫; シンボリ, クニオ; et al. (1996)
P(論文) 南極氷床の深層掘削を行うため, 国立極地研究所は掘削装置開発小委員会等を設け, 1988年以来開発研究を行ってきた。開発の経緯については, 中間報告, 深層掘削ドリルの最終仕様, その完成までの経過にわけて, それぞれ報告してある。本報告では開発した深層掘削システムとその周辺装置について, ドームふじ観測拠点の掘削場の配置, 掘削作業の流れを説明したのち, 各論において, ウインチ, ケーブル, マスト, 操作盤, チップ回収器等の開発の経緯を設計基準, 具体的設計, 製作の流れに準じて説明した。 A deep ice coring system for Dome Fuji project has been developed under a project coordinated by the National Institute of Polar Research. Three reports have been issued already, mainly about the development of the drill system. We report here on the drilling site and equipment such as winch, drilling cable, mast, control panels, chip caching tools (filter) and so on as well as the drill. This paper includes an outline of drilling site and work, progress of machine design and final specifications of the above equipment. departmental bulletin paper